2010
DOI: 10.1007/s10886-010-9769-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Phytotoxicity of Terpenes from Tectona grandis

Abstract: A study was carried out on the allelopathic potential of four forest species, Tectona grandis, Aleurites fordii, Gliricidia sepium, and Maytenus buxifolia. The most active species, T. grandis, was selected to perform a phytochemical study. A new compound, abeograndinoic acid, was isolated, and elucidation of its structure showed that this compound has an unusual carbon skeleton. A further 21 known terpenoids-including 4 sesquiterpenoids, 8 diterpenes and 9 triterpenes-also were isolated. A biosynthetic scheme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 36 publications
0
44
0
2
Order By: Relevance
“…It has been shown that members of Acacia-sensu lato contain amines, simple cyanogenic glycosides, cyclitols, essential oils, diterpenes, fatty acids in oilseeds, fluoroacetate, gums, non-protein amino acids, triterpenes, phytosterols, saponins, flavonoids and tannins; however, the identification of these compounds results from the study of a small number of species within this genus (Seigler 2003). Some of the above secondary metabolites have been associated with phytotoxic or inhibitory activity, for example alkaloids (Elakovich & Yang 1996, Hornoy et al 2012, Goyal 2013, cyanogenic glycosides (Carlsen & Fomsgaard 2008, Ambika 2013, terpenes (Ens et al 2009, Macias et al 2010, flavonoids (Carlsen & Fomsgaard 2008, Ambica 2013 and tannins (Carlsen & Fomsgaard 2008). Acacia dealbata Link (silver wattle, aromo) one of the most widely distributed species of the genus Acacia.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that members of Acacia-sensu lato contain amines, simple cyanogenic glycosides, cyclitols, essential oils, diterpenes, fatty acids in oilseeds, fluoroacetate, gums, non-protein amino acids, triterpenes, phytosterols, saponins, flavonoids and tannins; however, the identification of these compounds results from the study of a small number of species within this genus (Seigler 2003). Some of the above secondary metabolites have been associated with phytotoxic or inhibitory activity, for example alkaloids (Elakovich & Yang 1996, Hornoy et al 2012, Goyal 2013, cyanogenic glycosides (Carlsen & Fomsgaard 2008, Ambika 2013, terpenes (Ens et al 2009, Macias et al 2010, flavonoids (Carlsen & Fomsgaard 2008, Ambica 2013 and tannins (Carlsen & Fomsgaard 2008). Acacia dealbata Link (silver wattle, aromo) one of the most widely distributed species of the genus Acacia.…”
Section: Introductionmentioning
confidence: 99%
“…Th e extract was evaporated in a rotary evaporator under reduced pressure at 40°C. Th is extraction was repeated three times for each solvent (Macías et al 2010). Th us, the extracts obtained aft er fi ltering and drying were hexane, dichloromethane, ethyl acetate, acetone and methanol.…”
Section: Chemical Extractionmentioning
confidence: 99%
“…Th e next 4 mm of the coleoptile sections were removed and used for bioassay. All manipulations were performed under green safelight (Macías et al 2010).…”
Section: Wheat Coleoptiles Bioassaymentioning
confidence: 99%
“…Assim, estes compostos podem ser utilizados como herbicidas naturais ou servir de modelo para a síntese de produtos mais especíicos e menos prejudiciais ao ambiente (MACÍAS et al, 2010). Os herbicidas naturais possuem algumas vantagens sobre os sintéticos como a ausência de moléculas halogenadas em sua composição, menor meia vida, maior solubilidade em água (OLIVEIROS-BASTIDAS, 2008) e menor susceptibilidade de desenvolvimento de resistência das espécies infestantes (PINTO et al, 2008, NOVAES et al, 2013.…”
Section: Introductionunclassified